Aplikasi Pendekatan-Pendekatan Persuasif Pada Riset Komunikasi Pemasaran: Iklan Melibatkan Penciptaan dan Penerimaan Pesan Komunikasi Persuasif Mengubah Perilaku Pembelian - Putri, Primadhany Kartana (Universitas Semarang, 2016)
The study explain how to describe and apply Persuasion Theories in Advertising is typically define as human communication that is designed to influence others by modifying their beliefs, values, or attitude. Many theories of persuasif communication are concerned with shift in attitude is a relatively enduring predisposition to respond favorably or unfavorably toward something. The reseacher presents and compares the three theories of persuasion, the Elaboration Likehood Model (ELM), Cognitive Dissonance and Attribution that explore aspects of persuasive communication which are presented or examined in several previous studies. Although protayed as theories of persuasion, each of these point of viewpoints can be appiled to a wide variety communication messages delivered by marketers to influence and change consumer attitudes.The relevance theories bridges communication and cognition and, as such, provides a solid foundation for further research on persuasion, marketing communication, and many other aspects that influence consumer behavior.